CFD analysis of flow across adjacent buildings with concave roof structure using large-eddy simulation (LES) - Foo, Tze Jie (2017)
Currently, there is a growing trend towards green building, where buildings are designed to cater for the collection of rainwater for rooftop gardening. A method to achieve this is through the functional design of a concave roof structure that can act as a ‘bowl’ to collect the rainwater. On top of this application, the concave roof structure also provides a method of trapping onto the water instead of letting the rainwater flow down the roof, which can help reduce the chances of flash floods during heavy monsoon seasons. However, the collection of rainwater to impose certain loading onto the building and thus there is a need to perform a CFD analysis into the behaviour of the moving fluid flowing across the concave roof building.